UV-C treatment delays postharvest senescence in broccoli florets - Costa, M.lorenza (2006)
Central broccoli heads (cv. de Cicco) were harvested and treated with UV-C light (4, 7, 10, or 14 kJ m-2). All treatments delayed yellowing and chlorophyll degradation at 20°C but the irradiation dose of 10 kJ m -2 allowed retaining the highest chlorophyll content yet had lower amounts of pheophytins than every treatment other than 7 kJ m-2. This dose was selected to analyze the effect of UV-C on postharvest broccoli senescence at 20°C. The UV-C treatment delayed yellowing, chlorophyll a and b degradation, and also the increase in pheophytins during storage. The activity of chlorophyll peroxidase and chlorophyllase was lower in UV-C treated broccoli. Instead, Mg-dechelatase activity increased immediately after the treatment, but after 4 and 6 d this activity was lower in UV-C treated florets than in controls. Treated broccoli also displayed lower respiration rate, total phenols and flavonoids, along with higher antioxidant capacity. The results suggest that UV-C treatments could be a useful non-chemical method to delay chlorophyll degradation, reduce tissue damage and disruption, and maintain antioxidant capacity in broccoli. © 2005 Elsevier B.V. All rights reserved.